Happy birthday, Monster! - Beck, Scott (New York : Abrams Books for Young Readers, 2007)
Ben throws a surprise birthday party for his friend and fellow monster, Doris, complete with dancing, snacks, games, and presents.
A Junior Library Guild selection
Accelerated Reader/Renaissance Learning
1 5 8 12 13 18 29 33
Keywords: Birthdays -- Juvenile fiction; Parties -- Juvenile fiction; Monsters -- Juvenile fiction; Birthdays -- Fiction; Parties -- Fiction; Monsters -- Fiction; Picture books for children; Children's stories -- Pictorial works